The case for integrated transport and health surveillance in Wales - Jones, Sarah (International Journal of Population Data Science, 2019)
Background with rationale Transport is an under-recognised wider determinant of health. But, there is growing recognition, among policy makers and the general public, that significant modal shift, from cars and to greater use of public transport and active travel is needed to improve and protect health directly and indirectly, and in the short and long term, including with regards to climate change. In Wales, this comes when a new Welsh Transport Strategy is being written. This is likely to encourage greater recognition of the links between transport and health and demand data to support understanding of the ways in which transport affects health, as well as to evaluate the effects of the strategy, and to support wider research into the links between transport and health. Main Aim This suggests the need for a formal, routine transport and health surveillance system. This study will therefore aim to determine whether this is needed. Methods/Approach The approach is a review of existing systems and the evidence for the links between transport and health. Results This paper will present the results of the review noted above and outline the rationale for and structure of a Welsh Transport and Health Surveillance System that will support policy evaluation at local and national levels.